2013
DOI: 10.1002/lsm.22152
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of continence following 532 nm laser prostatectomy for patients previously treated with radiation therapy or brachytherapy

Abstract: In this pilot study, 532 nm GreenLight™ laser prostatectomy is feasible and safe in patients who have undergone prior radiotherapy for prostate cancer. Laser prostatectomy provides a durable response while maintaining continence in this cohort suffering from severe lower urinary tract symptoms (LUTS) or retention. Larger, randomized trials comparing GreenLight™ laser prostatectomy to traditional TURP are necessary to confirm non-inferiority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Earlier studies reported an 18-19 % risk of incontinence for TURP after radiation therapy [49,53], with some suggestion that late retention (TURP>2 years after brachytherapy) was a risk factor for incontinence. Other reports suggest a much lower risk of incontinence for both TURP and PVP after radiation therapy [50,52].…”
Section: Variables and Patient Characteristics That May Influence Thementioning
confidence: 95%
See 1 more Smart Citation
“…Earlier studies reported an 18-19 % risk of incontinence for TURP after radiation therapy [49,53], with some suggestion that late retention (TURP>2 years after brachytherapy) was a risk factor for incontinence. Other reports suggest a much lower risk of incontinence for both TURP and PVP after radiation therapy [50,52].…”
Section: Variables and Patient Characteristics That May Influence Thementioning
confidence: 95%
“…Additionally, PVP remains a reasonable alternative, which is also safe and effective [51,52]. Some authors have expressed concern regarding the relief of obstruction after radiation because of the risk of urinary incontinence in the setting of an overactive bladder, which may not have been fully appreciated.…”
Section: Variables and Patient Characteristics That May Influence Thementioning
confidence: 99%
“…Brachytherapy is an ideal treatment for clinically localized prostate cancer. When compared with radical prostatectomy, brachytherapy is often well-tolerated, with only mild to moderate urinary morbidity; however, urinary complications following brachytherapy, such as bladder-outlet obstruction or urinary retention, have been reported in up to 15% of the men that have undergone the procedure ( 1 ). Several alternatives for the treatment of post-brachytherapy retention have been reported in the literature, including prolonged suprapubic catheterization, intermittent self-catheterization, urethral endoprosthesis and transurethral resection of the prostate (TURP) ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%